TEACHING ENGLISH AT HIGHER EDUCATION IN INDONESIA: SEARCHING FOR USEFULNESS - Ummi Rokhyati (Universitas Negeri Padang, 2013)
Foreign language is one of compulsory subjects for every student including students at higher education to learn. English becomes the choice as a foreign language learnt in many universities in Indonesia. This is a good choice since up to now English is still an international language that is needed in global society. Higher education graduates live as members of global society and therefore are demanded to be able to communicate in English. However, if students learn it only for two credits during their time studying at universities can it meet the demand? What can the students learn from two credits of English? What should be taught? Teaching English in such situation sometimes makes the lecturers confused. Offering higher education students two credits of English is just like a formality. It is not really useful. The English teaching at higher education must be changed into one which contributes to the students’ success in the global communication using English. This paper will offer the ways how teaching English in higher education should be conducted. It will be started by discussing the policy of teaching foreign language in higher education made by the government. Then, examining the goals of teaching English and the materials taught to the students. If the usefulness is the target, a revision of teaching English to higher education students must be made.